CARDIAC ARREST IN THE EARLY POSTOPERATIVE PERIOD - Burmuzoska M; Toleska M; Leshi A; Kartalov A; Grncharevski M; Seljmani R (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University Skopje, R.N.Macedonia, 2021)
In-hospital cardiac arrest (IHCA) is determined as acute circulatory loss which requires fast resuscitation with chest compressions and/or defibrillation. Despite that it is a common condition, little research is done in this area, and many data are extracted from out-hospital cardiac arrest guidelines and researches. Perioperative cardiac arrest patients are a subclass of surgical patients who need CPR on the day of surgery. In this article, through a case report about successful reanimation, the in-hospital and perioperative cardiac arrest characteristics are discussed. A young female patient presented with cardiac arrest, 30 minutes after arriving in PACU and acute pulmonary embolism was the most suspected cause of the arrest. She was reanimated for around 30 minutes and she recovered without any neurological impairment. Perioperative cardiac arrest must be distinguished from other cardiac arrests and ACLS guidelines should be targeted according to particular situations. These patients require rapid evaluation and quick management, because usually there is a potentially reversible cause. As quickly as the cause is identified, as much the chances of ROSC are bigger